2015
DOI: 10.1111/imj.12665
|View full text |Cite
|
Sign up to set email alerts
|

No payments, copayments and faux payments: are medical practitioners adequately equipped to manage Medicare claiming and compliance?

Abstract: The complexity of Medicare claiming means it is often beyond the comprehension of many, including medical practitioners who are required to interpret and apply Medicare every day. A single Medicare service can be the subject of 30 different payment rates, multiple claiming methods and a myriad of rules, with severe penalties for non-compliance, yet the administrative infrastructure and specialised human resourcing of Medicare may have decreased over time. As a result, medical practitioners experience difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…6 Others may be unaware of the myriad legal obligations applicable to each claim, particularly when a single medical service in Australia can be the subject of more than 30 payment rates, multiple rules and strict penalties for non-compliance. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Others may be unaware of the myriad legal obligations applicable to each claim, particularly when a single medical service in Australia can be the subject of more than 30 payment rates, multiple rules and strict penalties for non-compliance. 7 …”
Section: Discussionmentioning
confidence: 99%
“…1 4 10 11 It has also been identified as an issue in Australia, 12 23 where the medical billing system is divorced from clinical designations (such as the ICD) and a single medical service can be the subject of over 30 different fees, rules and penalties. 7 There have been suggestions that education may improve billing literacy, 9 yet there has been scant research attention on training medical practitioners regarding correct medical billing. In response to the dearth of research in this area, this study attempts to systematically map all avenues of medical practitioner education on Medicare billing and compliance in Australia and explores the perceptions of medical education stakeholders on the teaching of medical billing in Australia to inform appropriate policy and regulatory initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is and was always an unrealistic and onerous requirement on medical practitioners given the current printed version of the MBS comprises over 900 A4 pages of item numbers, explanatory notes, rules and cross references, many of which are difficult to comprehend, and a single medical service can be the subject of over 30 different payment rates and rules. 26 We also found no evidence of medical billing educational resources such as a 25 year body of precedent that might assist medical practitioners to understand how to bill correctly.…”
Section: Discussionmentioning
confidence: 61%
“…This practice is evident in the current out-of-pocket medical fees crisis in Australia. 26 Another serious and potentially dangerous impact is that working under the constant threat of audits and investigation may cause some medical practitioners to under-service their patients.…”
Section: Discussionmentioning
confidence: 99%
“…14-16 This finding also aligns analysis of Australian medical billing policies which reported that a single Medicare service in Australia can be the subject of more than 30 different payment rates, multiple claiming methods and myriad rules. 17…”
Section: Discussionmentioning
confidence: 99%